Effectiveness of the Scientific Paper Writing Workshop in a New Medical College of Northeast States of India - Kishore, Jugal; Debnath, Aninda; Boro, Pallavi; Goutam, Soram; Singh, Toijam Gambhir (Journal of College of Medical Sciences-Nepal, 2024)
Background Academic paper writing is crucial for medical professionals, facilitating effective communication, critical thinking, and scholarly contributions in medicine. Proficient writing is vital as it influences knowledge dissemination, evidence-based practices, and medical research advancement. The objective of the current study was to assess the effectiveness of academic writing workshops for medical professionals. Methods The workshop conducted during SAPHCON 2023 spanned four hours and consisted of seven sessions on various aspects of academic writing and publication. Participants completed pre-test and post-test assessments to evaluate changes in their knowledge and comprehension. Statistical analysis using SPSS software was employed to measure the intervention's effectiveness. Results The workshop involved 21 participants who completed both pre-test and post-test questionnaires. Of the participants, 25% were male, and 75% were female, with a mean age of 33.8 (SD = 6.3) years. The post-test analysis revealed an overall increase in the proportion of correct answers for most of the questions. The pre-test median score was 7 (IQR 6-10), and the post-workshop test median score was 10 (IQR 9-11), indicating a significant increase in the median score (p=0.02). Conclusions The post-test results showed a significant improvement in the median score compared to the pre-test, indicating enhanced knowledge among participants. The study's findings aligned with previous investigations, highlighting the workshop's positive impact on knowledge enhancement. Our study contributes valuable insights into the effectiveness of manuscript writing workshops in the Indian context, laying the groundwork for future research with larger sample sizes and diverse populations, and exploring long-term impacts.